The Effect of Pressure Injury Training for Nurses: A Systematic Review and Meta-analysis. (March 2020) - Park, Mikyung; Kim, Gaeun; Kim, Kyungwon
ABSTRACT: OBJECTIVE: To conduct a meta-analysis of the literature on training programs that aimed to improve nurses' pressure injury management skills. METHODS: Literature searches were conducted using Ovid-MEDLINE, Cochrane Library, CINAHL, and Korean databases. The search terms used were: (nurse* AND ((pressure OR decubitus) AND (ulcer* OR injur*)) OR bed sore OR bedsore OR decubitus) AND (program* OR training)). Random-effects models were used to calculate the standardized mean difference and odds ratios, with 95% confidence intervals (CIs) to analyze the effects. MAIN RESULTS: Initial searches yielded 1, 067 studies. Of these, 23 met the selection criteria. Nurses' knowledge (standard mean difference, 1.23; 95% CI, 0.50-1.96; P < .001), visual discrimination ability (standard mean difference, 1.13; 95% CI, 0.88-1.38; P < .001), and clinical judgment (odds ratio, 1.52; 95% CI, 1.46-1.57; P < .001) improved after the programs. CONCLUSIONS: Pressure injury training programs can improve nurses' competency. The results from this study indicate that such programs may help improve nurses' knowledge, visual discrimination ability, and clinical judgment and can be considered continuing education programs. However, large-scale studies are needed to confirm this conclusion.